Menin and MLL cooperatively regulate expression of cyclin-dependent kinase inhibitors. - Milne, T; Hughes, C; Lloyd, R; Yang, Z; Rozenblatt-Rosen, O; Dou, Y; Schnepp, R; Krankel, C; Livolsi, V; Gibbs, D; Hua, X; Roeder, R; et al. (2005)
Mutations in the MEN1 gene are associated with the multiple endocrine neoplasia syndrome type 1 (MEN1), which is characterized by parathyroid hyperplasia and tumors of the pituitary and pancreatic islets. The mechanism by which MEN1 acts as a tumor suppressor is unclear. We have recently shown that menin, the MEN1 protein product, interacts with mixed lineage leukemia (MLL) family proteins in a histone methyltransferase complex including Ash2, Rbbp5, and WDR5. Here, we show that menin directly regulates expression of the cyclin-dependent kinase inhibitors p27Kip1 and p18Ink4c. Menin activates transcription by means of a mechanism involving recruitment of MLL to the p27Kip1 and p18Ink4c promoters and coding regions. Loss of function of either MLL or menin results in down-regulation of p27Kip1 and p18Ink4c expression and deregulated cell growth. These findings suggest that regulation of cyclin-dependent kinase inhibitor transcription by cooperative interaction between menin and MLL plays a central role in menin's activity as a tumor suppressor.